Compatibility conditions for microstructures and the austenite-martensite transition - Ball, J; Carstensen, C (1999)
We explore theoretically the possibility of austenite-martensite transformations more complicated than those envisaged by the crystallographic theory, and make corresponding experimental predictions. The use of the Hadamard jump condition in this context is justified, and leads also to results on non-attainment of minimum energy. (C) 1999 Elsevier Science S.A. All rights reserved.